KONTRIBUSI KETERAMPILAN MENYIMAK TEKS CERITA MORAL/FABEL DENGAN KETERAMPILAN MENULIS TEKS CERITA MORAL/FABEL - Caprita, Putri Siltya; Nursaid, Nursaid; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This article was written to discuss the results of research on the skills to the text story moral/fable with writing skills the text story moral/fable the students class VIII SMP Negeri 5 Pariaman. The research was a score of the results of the skills to the text story moral/fable and a score of results of the writing skills the text of story moral/fable. The data obtained through two types of test, which isthe objective of a multiple choice as much as 40 bullets to measure the level of skills to the text story moral/fable and work performance for the skills writing the strory text moral/fable. This type of this study is quantitative. The method used is the method of descriptive with the design of merely correlational. The result of this research, there were three, that is (1) skills to te text story moral/fable the student class VIII in elementary school 5 Pariaman on qualifications (80,93), (2) the skill of writing the text story moral/fable the stuents class VIII in elementary school 5 Pariaman, located in the qualifying well (80,79), and (3) by the skills to the text story moral/fable to contribute with writing skills the text story moral/fable the students class VIII in elementary school 5 Pariaman as much as 54,61% in other words to te text story moral/fable it takes skill to text story moral/fable.Â Kata kunci : kontribusi, keterampilan menyimak, keterampilan menulis